Mitochondrial population structure of false killer whales (pseudorca crassidens) and pilot whales (globicephala melas) around new zealand waters, genetic diversity and initial evidence of hybridization (2021)
The long fin pilot whale (Globicephala melas) and the false killer whale (Pseudorca crassidens) are two social delphinid species that travel in big groups and have strong matrilineal associations. Previous studies found low levels of genetic diversity in both species. Here, we use mitochondrial DNA (mtDNA) control region sequences and genotypes from seven nuclear DNA (nucDNA) microsatellite loci, to examine the genetic diversity and population structure of both species from skin samples collected around New Zealand waters. We also analyze the presence of a possible hybrid between G.melas and other delphinids, using genetic and photographic evidence. In concordance with previous studies, relatively low levels genetic diversity were found for both species. We described a new G.melas control region haplotype, unique to the Bay of islands location (BOI) in New Zealand and found significant differentiation between the BOI location and a different New Zealand location from a previous study. All P.crassidens control region sequences obtained in this study corresponded to a previously defined haplotype from the South Pacific. Morphological differences between G.melas and the possible hybrid individuals were observed, however, no genetic evidence of hybridization between G.melas and P.crassidens was found. The sample corresponding to the possible hybrid was identified as Globicephala macrorhynchus based on mitochondrial DNA. Our findings indicate that in the North Island of New Zealand, the distribution of both pilot whale species can eventually overlap. Further analysis must be performed to confirm if this case could be a hybridization event between G.melas and G.macrorhychus.